Safety study of Herbified® shilajit resin - Iqubal, Ashif; Sharma, Sumit; Bansal, Priyanka; Ali, Athar; Khan, Nausheen; Qadir, Abdul (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Shilajit is an ancient herbo-mineral compound with numerous proven health benefits. In recent times, Shilajit has been extensively studied in preclinical and clinical models to validate its documented effects. However, there are very few preclinical safety studies from India, and they are scattered. Methods: In the present study, we evaluated the safety of Herbified® Shilajit resin in a subacute oral toxicity study in Wistar rats. The study was conducted for 28 days for the treatment and control groups. For the satellite control and satellite reversal group, the study was extended for an additional 14 days. In the current manuscript, we documented body weight, biochemical and hematological parameters, and histopathological analysis of vital organs in male and female groups. Results: The study showed that treatment with low-, moderate-, and high-dose Herbified® Shilajit was safe, and outcomes across all parameters were comparable to those of the control group. Also, the outcomes in the satellite control and satellite reversal groups were similar to those in the control group. Conclusions: Based on the results of this study, 206.65 mg/kg, p.o., of Shilajit in rats is safe, equivalent to approximately 2000 mg of Shilajit for an adult human (60 kg).